"Don’t Tell Me How to-Dance!": Negotiating Collaboration, Empowerment and Politicization in the Ethnographic Theatre Project "Hope" - Kazubowski-Houston, Magdalena (Anthropologica, 2022)
This article contributes to the experimental ethnog- raphy literature by providing a critique of ethnographic col- laboration, empowerment and politicization. Focusing on my ethnographic theatre project "Hope" - developed in collabora- tion with Roma women and local actors in Poland in 2003 - I discuss the power struggles over representation that defined my project and that arose from our multifarious understand- ings of theatre as an art form, differences in what the project meant to us and in what we hoped to accomplish through it. I reveal the problematic moral, ethical and political decisions I had to make that forced me to rethink both my methodology and my role as ethnographer.